The effectiveness of maintenance management of services in shopping complex building : Plaza Alam Sentral, Shah Alam / Syed Mohamad Fahmi Wafa Syed Jalaluddin - Syed Jalaluddin, Syed Mohamad Fahmi Wafa (2009)
Maintenance Management is a combination of several actions in which to retain or restore an item to perform its required action. Plaza Alam Sentral Shah Alam as a Shopping Complex is one of the main commercial building in Klang Valley that has many building services, thus needs maintenance to prevent the assets from deterioration. Maintenance in Plaza Alam Sentral Shopping Complex was monitored and controlled by MRCB Sentral Properties Sdn. Bhd. and Semasa Services Sdn. Bhd. There are three maintenance system presently implemented at Plaza Alam Sentral building : Planned Preventive maintenance, Curative Maintenance and Emergency Maintenance. The maintenance of the services system is carried out by combination of in house and outsources contractors. Aim of this study is to recommend a step to improve the effectiveness of the maintenance management system to this shopping complex building especially in the aspect of building services. To achieve the aim of this study, four objective has been setting up. The objectives are to study the maintenance management that presently implemented in shopping complex buildings, to find out the satisfactory levels of tenants in the shopping complex building, to measure the effectiveness of maintenance management of the services system in the buildings as a commercial shopping complex and to give recommendation on improving the quality and maintenance management of services systems in shopping complex buildings. This research focused on the greatest shopping complex building in Shah Alam at current time. To obtain the data the following knowledge acquisition methods were used that is by literature review, interview, and questionnaires. The result shows that the current performance of the building services provided cannot fulfill the tenants’ needs and satisfaction. Some recommendation has been provided to improve the effectiveness of the maintenance management of the building.